Persepsi Mahasiswa Terhadap Penggunaan Media Sosial Youtube Sebagai Media Content Video Creative (Studi Kasus Deskriptif Kualitatif Pada Mahasiswa Ilmu Komunikasi Angkatan 2018) - Jepri Adrianto; Hasan Sazali; Abdul Rasyid (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2023)
This study aims to find out how YouTube has an effect on students through their respective perceptions. This type of research uses descriptive qualitative, namely research that reveals certain social situations by describing reality correctly formed by words based on relevant data collection and data analysis techniques, while the data sources used in this research are primary and secondary data sources with a number of informants. as many as 8 people. Data collection techniques used are interview documentation, and observation.The results of the research conducted show that YouTube is able to have quite an influential effect on the lives of people who use YouTube. This effect can be a positive effect or a negative effect for the user.